2015
DOI: 10.1002/jsid.396
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 8K4K organic EL panel using high-mobility IGZO material

Abstract: A 13.3-inch 8k4k organic light-emitting diode display based on a newly developed highmobility indium-gallium-zinc-oxide material was fabricated. It was found that the use of a highermobility material decreases the scan driver size and power consumption. Furthermore, such oxide semiconductor layers with a buried channel structure can increase process stability and reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Our previous s having an In-rich of In:Ga:Zn 1 eliability [9,10] FET including a are stacked to damage during th FET including a ayer achieves a These reports s active layer havin 4.1 can possibl fabricated and ev ayer with the Instructure in whic…”
Section: Backgroumentioning
confidence: 99%
“…Our previous s having an In-rich of In:Ga:Zn 1 eliability [9,10] FET including a are stacked to damage during th FET including a ayer achieves a These reports s active layer havin 4.1 can possibl fabricated and ev ayer with the Instructure in whic…”
Section: Backgroumentioning
confidence: 99%
“…Hence, there are only a few mass production factories of large panel. In contrast, a lot of studies have reported about improving photo‐stability, such as c‐axis‐aligned crystal‐indium gallium zinc oxide and dual gate …”
Section: Introductionmentioning
confidence: 98%
“…In the authors' previous study, high-mobility IGZO with In:Ga:Zn ratio = 4:2:3 (IGZO(4:2:3)) was prepared and high field-effect mobility and reliability were achieved using IGZO(4:2:3) [4][5][6][7]. Ito et al recently reported high-mobility IGZO with a Hall mobility of 50 cm 2 /Vs [8].…”
Section: Introductionmentioning
confidence: 99%